How can market mechanisms for forest environmental services help the poor?: preliminary Lessons from Latin America - Grieg-Gran, M.; Porras, I.; Wunder, Sven (2005)
Market mechanisms for forest environmental services are a new approach for conservation, but there is also an increasing interest in the derived developmental benefits of these mechanisms. We first propose a conceptual framework for future research on the livelihood impacts of environmental service markets. We then review eight Latin American case studies on carbon sequestration and watershed protection market initiatives, finding positive local income effects in most cases, more land tenure security and socioinstitutional strengthening in some cases, but some negative effects also. We recommend pro-poor policy measures such as reducing smallholders’ transaction costs and removing inappropriate access restrictions.